Նատրիումի վալպրոատի ռեգիոնալ ազդեցությունը արգինինի ենթաբջջային նյութափոխանակության և լիպիդների գերօքսիդացման գործընթացների վրա գլխուղեղում փորձարարական երկբևեռ խանգարման ժամանակ - Մ. Ռ. Հովհաննիսյան (ՀՀ ԳԱԱ հրատ.)
Впервые продемонстрировано модулирующее влияние вальпроата натрия (VPA) на активность изоформ аргиназы в цитоплазме и митохондриях регионов кортиколимбической системы при дексамфетамин-индуцированном биполярном расстройстве. VPA резко подавляет процессы перекисного окисления липидов, посредством чего оказывает регион-специфическое регулирование изоформ аргиназы и защищает от дексамфетамин-индуцированных гистопатологических сдвигов в структурах мозга. We show for the first time the modulatory effects of sodium valproate (VPA) on the arginase isoforms activities in cytoplasm and mitochondria in the regions of corticolimbic system following AMPH-induced bipolar disorder. VPA decreases drastically lipid peroxidatian processes there through mediates region-specific regulation of arginases and protection against AMPH-induced histopathological changes in the brain structures.
Keywords: Internal medicine; Neuroscience; Biological psychiatry; Neuropsychiatry; Brain diseases